Sistem Kontrol Otomatis Pemberian Larutan Nutrisi untuk Tanaman Kale Pada Metode Pertanian Aeroponik Berbasis Mikrokontroler - Magfira Ardani; Nini Firmawati; Rahmat Rasyid (Universitas Andalas, 2026)
Innovation in agricultural cultivation methods continues to be developed to improve production yields, one of which is the aeroponic system that enables plants to grow without soil media. This study designs and implements a prototype of an automatic control system for nutrient solution delivery in kale cultivation using an aeroponic method. The system is equipped with a DHT22 sensor for temperature and humidity monitoring, a TDS sensor for nutrient concentration measurement, and a JSN-SR04T sensor for solution level detection. The actuators include a fan cooler, a DC water pump, and two mini DC pumps, all operating automatically based on sensor data. The fan cooler is activated at temperatures above 26 °C, the mist nozzle sprays the solution when humidity drops below 88% or periodically every 10 minutes, while the mini DC pumps maintain the nutrient concentration and solution level within optimal ranges. Testing was conducted over 29 days with data recorded at 07:15, 12:00, 16:00, and 20:00. The results show that the system can operate automatically, stably, and effectively in maintaining environmental conditions that support the growth of kale plants in an aeroponic system.